RANCANGAN ANTENA MIKROSTRIP DIPOLE PADA PERANGKAT PORTABLE ILS/VOR RECEIVER FREKUENSI 328,6 MHz SAMPAI 335,4 MHz - Ester Mella; Muh. Wildan; Benny Suherman (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
The activity of checking instrument landing system equipment, one of which is monitoring the beam results using Portable ILS / VOR Receiver (PIR). The design of the microstrip dipole antenna is intended to get a smaller device, because the PIR antenna that has been used so far is a dipole antenna that has a long enough dimension for portable devices. This microstrip antenna is designed on the ILS Glidepath frequency, which is in the frequency range 328.6 MHz to 335.4 MHz. The simulation results of microstrip dipole antenna show good performance and meet specification standards. At the 332 MHz frequency, return loss (S11) is obtained at -25.425 dB, 10 MHz bandwidth, 1.11 VSWR, 50 masukan input impedance, linear polarization, and omnidirectional radiation pattern. While the measurement results obtained are at 332 MHz frequency, return loss (S11) of -20.24 dB, bandwidth of 10 MHz, and VSWR 1.21